2016
DOI: 10.14814/phy2.12886
|View full text |Cite
|
Sign up to set email alerts
|

Extrapancreatic effects of incretin hormones: evidence for weight‐independent changes in morphological aspects and oxidative status in insulin‐sensitive organs of the obese nondiabetic Zucker rat (ZFR)

Abstract: Incretin‐based therapies are widely used to treat type 2 diabetes. Although hypoglycemic actions of incretins are mostly due to their insulinotropic/glucagonostatic effects, they may also influence extrapancreatic metabolism. We administered exendin‐4 (Ex‐4), a long‐acting glucagon‐like peptide receptor agonist, at low dose (0.1 nmol/kg/day) for a short period (10 days), in obese nondiabetic fa/fa Zucker rats (ZFRs). Ex‐4‐treated ZFRs were compared to vehicle (saline)‐treated ZFRs and vehicle‐ and Ex‐4‐treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Measurement of individual muscle fiber diameter revealed a significant loss in SOD1 G93A mice as compared to WT mice (P = 0.00001), which was partially corrected in P110-treated G93A mice, indicating decreased atrophy (P = 0.0003) (Fig 4B and E). Since previous studies have attributed muscle atrophy with increased oxidative stress, we determined 4-hydroxy-2-nonenal (4-HNE) adducts on proteins in gastrocnemius muscle (Russell et al, 2003;Colin et al, 2016). 4-HNE is a nine-carbon amphiphilic lipidderived aldehyde formed by oxidation of nÀ6 polyunsaturated fatty acids.…”
Section: Embo Molecular Medicinementioning
confidence: 99%
“…Measurement of individual muscle fiber diameter revealed a significant loss in SOD1 G93A mice as compared to WT mice (P = 0.00001), which was partially corrected in P110-treated G93A mice, indicating decreased atrophy (P = 0.0003) (Fig 4B and E). Since previous studies have attributed muscle atrophy with increased oxidative stress, we determined 4-hydroxy-2-nonenal (4-HNE) adducts on proteins in gastrocnemius muscle (Russell et al, 2003;Colin et al, 2016). 4-HNE is a nine-carbon amphiphilic lipidderived aldehyde formed by oxidation of nÀ6 polyunsaturated fatty acids.…”
Section: Embo Molecular Medicinementioning
confidence: 99%
“…Other effects are suggestive of glucose‐independent effects of GLP‐1R agonists on muscle. Colin et al showed that myocytes from obese, nondiabetic Zucker rates were significantly enlarged and depleted of lipid droplets with exendin‐4 treatment, secondary to modulation of oxidative stress; Takada et al showed improved mitochondrial function and exercise capacity in mice receiving exendin‐4 . Exenatide was reported to prevent sarcoma‐induced cachexia in a mouse model, while liraglutide was shown to improve skeletal muscle capillary density in an animal model of insulin resistance, indicating a protective role against metabolic insulin resistance at the skeletal muscle level .…”
Section: Drugs and Musclementioning
confidence: 99%